Talk and Write your mathematical Thinking - Gilang Kian Ishaya; Rosalina Rolina; Desy Tri Damayanti (IKIP Siliwangi, 2018)
This research is motivated by the low mathematical communication skills of junior high school students in the city of Bandung Regency. This study aims to determine the comparison of the mathematical communication skills of junior high school students in the city of Bandung regency between the learning usingmodels Think Talk Write. The method used in this study is a quasi-experimental method with a pretest-posttest control group design involving two groups and randomly selected classes, at the beginning and end of the study the two classes were given a test. The population in this study were junior high school students in the city of Bandung Regency, while the sample consisted of two randomly selected classes. Obtained class VII A (experimental class) given themodel Think Talk Write and class VII B (control class) is given a scientific approach. The instrument used was a 5-item mathematical communication ability description test, then theability scores mathematical communication students'were analyzed with descriptive and inferential statistics using the help of SPSS 21 software. Based on the results of the study, it was concluded that there were differences in the achievement of students' mathematical communication skills using models Think Talk Write with students who used a scientific approach.